Effects of preemptive analgesia in laparoscopic cholecystectomy: A double-blind randomized controlled trial - Trichak Sandhu (2018)
Background: This study aimed to investigate the effect of preemptive etoricoxib compared with placebo in laparoscopic cholecystectomy. Methods: This randomized, double-blind, placebo-controlled study enrolled 120 patients requiring elective laparoscopic cholecystectomy. The patients were randomized to receive either etoricoxib 120 mg plus diazepam or placebo plus diazepam. Postoperatively, the visual analog score (VAS) for pain, the rescue morphine requirement, and the side effects were recorded. Results: Between February 2006 and September 2007, 120 patients were enrolled in the study. The demographic data between two groups were similar except for mean age. The mean age of the placebo group was younger (p = 0.007). There were no significant differences in bleeding tendency rating scores, duration times between fentanyl and rescue morphine, number of rescue morphine doses, or length of postoperative hospital stay. But the number of oral analgesic drug usages was significantly less in the etoricoxib group (p = 0.006). The postoperative VAS was lower in the etoricoxib group at hours 10 (p = 0.023), 14 (p = 0.045), and 26 (p = 0.011), and the average VAS also was significantly less in the etoricoxib group (p = 0.013). The two groups did not differ significantly in terms of postoperative shoulder pain (p = 0.065). According to the verbal rating scale, the incidence of postoperative nausea and vomiting did not differ significantly between the two groups (p = 0.797), nor did the drug side effects or treatment complications. Conclusion: The authors recommend using etoricoxib as a preemptive analgesia to reduce postoperative pain after laparoscopic cholecystectomy. © 2010 Springer Science+Business Media, LLC.